REDESIGN ERGONOMIC RUBBISH BIN EFFICIENT BASED ON ANTHROPOMETRY DATA - Sari, Resy Kumala; Tabagus, Raka (Research Center University of Pahlawan Tuanku Tambusai, 2021)
Abstract The rubbish bin is needed globally because of the place to collect the rest of the rubbish. The rubbish bin is available in the public area, home, and office. This study redesigned the Rubissh bin to make it more ergonomic and efficient when used and recruited 100 students of Universitas Pahlawan Tuanku Tambusai (45 female participants and 55 male participants) by measuring their anthropometry of the human body. Anthropometric data measured in the form of Lebar Bahu (LB), Tinggi Kepalan Tangan (TKT), Tinggi Pinggang Berdiri (TPB), Lebar Telapak Tangan (LTT), Lebar Telapak Kaki (LTK), and Jangkauan Tangan Kedepan (JTD). After that, the data in the normality test can be seen that the chi-square